Chronic NaHS Treatment Is Vasoprotective in High-Fat-Fed ApoE−/− Mice - Asha Ford; Mohammad Al-Magableh; Tracey A. Gaspari; Joanne L. Hart (International Journal of Vascular Medicine)
Hydrogen sulfide is emerging as an important mediator of vascular function that has antioxidant and cytoprotective effects. The aim of this study was to investigate the role of endogenous H2S and the effect of chronic exogenous H2S treatment on vascular function during the progression of atherosclerotic disease. ApoE−/− mice were fed a high-fat diet for 16 weeks and treated with the H2S donor NaHS or the cystathionine-γ-lyase (CSE) inhibitor D,L-propargylglycine (PPG), to inhibit endogenous H2S production for the final 4 weeks. Fat-fed ApoE−/− mice displayed significant aortic atherosclerotic lesions and significantly impaired endothelial function compared to wild-type mice. Importantly, 4 weeks of NaHS treatment significantly reduced vascular dysfunction and inhibited vascular superoxide generation. NaHS treatment significantly reduced the area of aortic atherosclerotic lesions and attenuated systolic blood pressure. Interestingly, inhibiting endogenous, CSE-dependent H2S production with PPG did not exacerbate the deleterious vascular changes seen in the untreated fat-fed ApoE−/− mice. The results indicate NaHS can improve vascular function by reducing vascular superoxide generation and impairing atherosclerotic lesion development. Endogenous H2S production via CSE is insufficient to counter the atherogenic effects seen in this model; however exogenous H2S treatment has a significant vasoprotective effect.